2015
DOI: 10.1371/journal.pone.0143336
|View full text |Cite
|
Sign up to set email alerts
|

Genome Analysis of Staphylococcus agnetis, an Agent of Lameness in Broiler Chickens

Abstract: Lameness in broiler chickens is a significant animal welfare and financial issue. Lameness can be enhanced by rearing young broilers on wire flooring. We have identified Staphylococcus agnetis as significantly involved in bacterial chondronecrosis with osteomyelitis (BCO) in proximal tibia and femorae, leading to lameness in broiler chickens in the wire floor system. Administration of S. agnetis in water induces lameness. Previously reported in some cases of cattle mastitis, this is the first report of this po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
116
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(126 citation statements)
references
References 47 publications
(75 reference statements)
3
116
0
1
Order By: Relevance
“…Interestingly, the genus Staphylococcus is one of the 18 features (including 3 genera) significantly enriched in BCO samples, which highlights the importance of this genus that has been frequently isolated from BCO lesions 3 4 5 . Recently Al-Rubaye et al 44 reported that the challenge of broilers with S. agnetis , which was most frequently isolated Staphyloccous species from BCO legions in their study, significantly increased lameness from 10 (Control) to 40%, while the challenge with another isolate Enterococcus faecalis decreased the lameness incidence. It may signify the potential importance of S. agnetis as the causative agent of BCO pathogenesis in broiler chickens, although our 16S rRNA gene profiling data failed to provide meaningful information on Staphylococcus species due to the limited resolution of taxonomic assignment.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, the genus Staphylococcus is one of the 18 features (including 3 genera) significantly enriched in BCO samples, which highlights the importance of this genus that has been frequently isolated from BCO lesions 3 4 5 . Recently Al-Rubaye et al 44 reported that the challenge of broilers with S. agnetis , which was most frequently isolated Staphyloccous species from BCO legions in their study, significantly increased lameness from 10 (Control) to 40%, while the challenge with another isolate Enterococcus faecalis decreased the lameness incidence. It may signify the potential importance of S. agnetis as the causative agent of BCO pathogenesis in broiler chickens, although our 16S rRNA gene profiling data failed to provide meaningful information on Staphylococcus species due to the limited resolution of taxonomic assignment.…”
Section: Discussionmentioning
confidence: 83%
“…As the coagulase homologue was only present in one isolate, acquisition via horizontal gene transfer seems more likely than a convergently evolved coagulase homologue. Staphylococcal species with variable coagulase phenotypes and genotypes have previously been reported, such as S. agnetis isolated from bovine mastitis samples and broiler chickens (Taponen et al, 2012;Al-Rubaye et al, 2015). It is interesting that the coagulase-positive isolate was only positive when tested with feline plasma.…”
Section: Discussionmentioning
confidence: 96%
“…Because approximately more than half of the isolates classified as S. hyicus, based on phenotypic speciation methods, were reclassified as S. agnetis using more precise molecular methods ( Adkins et al, 2017 ), it is likely that at least part of the S. agnetis isolates also have the capacity to cause a significant inflammatory reaction in the udder. Recently, S. agnetis was also shown to be the causative agent in bacterial chondronecrosis with osteomyelitis leading to lameness in broiler chickens in the wire floor system ( Al-Rubaye et al, 2015 ) and a potential causative agent in endocarditis and septicemia in broiler breeders ( Poulsen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%